Implementasi Algoritma Apriori Untuk Menentukan Frequent Itemset Pada Transaksi Penjualan di Apotik Galih - Perdana Gunawan Manik (Jurnal Ilmu Teknik dan Komputer, 2020)
Galih Pharmacy is one of the pharmacy in Kalisari area that sells complete medicine and sells medicines with affordable price. Every day, Galih Pharmacy sells many different type of medicines so that often happen excess stock or lack stock in restocking the medicines. If the stock in the warehouse not sold, the pharmacy’s party required to return the unsold medicine because it has passed the expire date. The purpose of this research to make medicine selling application with java programming language. This research done by applying or implementing Apriori algorithm which works to determine the value of Frequent Itemset, Support, and Confidence. The result of this research which the research have done according to sales transaction of the medicine by implementing apriori algorithm for Konidin, Amoxilin and Sanaflu. The medicines have value of support and confidence which exceds 40%. The conclusion obtained by the researcher that a Apriori algorithm can help entrepreneur in determining the number of quantity that must be stocked by the seller in accordance with the largest percentage level (possibility) in selling items every day.